FACTOR ANALYSIS OF STUDENT PRACTICUM IMPLEMENTATION ON LATHE WORK - Masnah, Siti Laily; stefhen, Gilbert; Solehudin, Agus; Putri, Amalia Aisyah (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2021)
Practical-based learning can improve students' thinking skills and abilities. Optimizing the implementation of the practicum needs to be supported by various factors so that student learning outcomes are good. This study aims to obtain the dominant factors that support the implementation of student practicum on lathe work. This study uses descriptive quantitative methods with data collection techniques using a questionnaire instrument. The research population is students from the Mechanical Engineering Education Study Program at a university in Bandung. The results of the study indicate that there is a relationship between a number of independent variables. The six independent variables identified as sources of practicum support were then grouped into two new factors. The two factors have a correlation greater than 0,5, so it can be concluded that it is feasible to summarize the six variables analyzed. Based on the total variance score explained, factor 1 is the dominant factor affecting the implementation of the lathe work practicum and according to the rotated component matrix it is known that from factor 1, the workshop building variable has the highest correlation and the tools and practicum materials have the second highest correlation. This shows that the variables of the workshop building and the variables of tools and practicum materials are very important to be used as references in supporting good learning outcomes in practical activities.